Guanidinium‐Based Ionic Covalent Organic Porous Polymer as Natamycin Delivery Agents for Anti‐Candida albicans. Issue 40 (20th October 2021) - Liu, Xia; Zhang, Fang; Lou, Han; Luo, Haotian; Peng, Cheng; Zhu, Shourong; Zhou, Baolong
Abstract: Here, we have strategically prepared a biodegradable ionic covalent organic porous polymers (ICOP) with dynamic double selenium bond (Se−Se) which was further used as carriers for the antifungal drug‐natamycin (NAT). ICOP presents a high drug‐loading capability (DL) of 79.33±0.12 %, as well as high encapsulation efficiency (EE) of 76.75±0.58 % to NAT. Meanwhile, owning to the simultaneous introduction of −Se−Se− bond and imine linkage, the composite drug delivery system are responsive to pH, with selective and sustained release in acidic media (pH=5.5), almost 1.34 fold as much as that in neutral conditions (pH=7.4). This special drug release behavior is consisted well with the optimum growing environment of candida albicans (pH=5.5), in which, more drugs could be released continuously, enhancing the duration of drug interactions with fungi and inhibiting the growth of fungus effectively. This novel dosing strategy is promising for the development of intelligent drug delivery system which could avoid the overdoses of drugs, and reduce the emergence of resistant strains. Abstract : A Diselenium‐bridged ionic covalent organic porous polymers (ICOP) was prepared which could be used as the carriers for the encapsulation of NAT. The NAT‐ICOP drug delivery system showed higher cumulative release of NAT in acidic media (pH 5.5), which could enhance the action time of drugs with fungus, thus, realizing selective treatment of infections caused by C. albicans.